Fragile X syndrome, the search for a targeted treatment - Shimriet Zeidler; Rob Willemsen (Faculty of Medicine, Diponegoro University, 2019)
Fragile X syndrome (FXS), the most common monogenetic cause of intellectual disability and autism spectrum disorders, is characterized by behavioral and physical problems. There is currently no adequate treatment available. While animal model studies seemed extremely promising, no success has been achieved in the larger clinical trials with human FXS patients. This short review describes the steps that have been taken in the development of a targeted treatment for FXS. Possible reasons for the lack of translation between animal models and human FXS patients are being explored and solutions are being proposed. The FXS story illustrates pitfalls and possibilities in translational research, that might especially be applicable for other neurodevelopmental disorders as well.